Development communication : reframing the role of the media - McPhail, Thomas L.; Wiley InterScience (Online service) (Chichester, U.K. ; Malden, MA : Wiley-Blackwell, 2009)
In Development Communication, top media scholars explore the details of communication in areas where modernization has failed to deliver change.:.; Offers a complete introduction to the history of development communication - the process of systematically intervening with either media or education in order to promote positive social change.; Discusses themajor approaches and theories in development communication, including educational issues of training, literacy, schooling, and use of media from print and radio to video and the internet.; Explores the role of NGOs, the CNN Effect, and the pow.
Development Communication: Reframing the Role of the Media; Contents; Tables and Figures; Notes on Contributors; Preface; 1: Introduction to Development Communication; 2: Major Theories Following Modernization; 3: United Nations and Specialized Agencies; 4: The Roles of Non-Governmental Organizations (NGOs); 5: Differing Views of World Culture; 6: A Framework for Conceptualizing Technology in Development; 7: The Global Digital Divide; 8: Feminism in a Post-Development Age; 9: Sonagachi Project: A Case-Study Set in India; 10: Roma Project: A Case Study Set in Europe.
Includes bibliographical references (pages 211-234) and index.
Print version record.
Keywords: Communication -- Social aspects; Mass media -- Developing countries; Telecommunication -- Developing countries; Mass media; Telecommunication; Communication; SOCIAL SCIENCE -- Media Studies; Communication -- Social aspects; Mass media; Telecommunication; Developing countries; Kommunikation -- sociala aspekter; Massmedia -- U-länder.; Electronic books